Панорамно-алгоритмічний метод мотивації навчання - Кучеренко, Сергій Михайлович; Лях, Бенгард Григорович; Сичов, Юрій Іванович; Литвиненко, Ігор Іванович; Самчук, Володимир Володимирович (НТУ "ХПІ", 2011)
The article deals with panoramic-algorithmic method of motivation to learn, whichmakes it possible to achieve the psychological comfort of students and contributes to the harmonious development of personality and goovnosti for professional work,which is a source of confidence for the future of healthy life.
Keywords: мотивація; психодіагностування мотивації; панорамно-алгоритмічна картина; технології мотивації